1991
DOI: 10.1088/0031-8949/43/1/018
|View full text |Cite
|
Sign up to set email alerts
|

Obliquely propagating ion-acoustic double layers in a multicomponent magnetized plasma

Abstract: Considering the appropriate coordinate transformation and charge separation effect, the reductive perturbation method is used to derive a mKdV equation for a multi-component magnetized plasma having two Maxwellian electron distributions and two warm adiabatic ion distributions. The double layer solution of the mKdV equation is discussed in detail. It is found that the width of the double layer increases as we increase the obliqueness 6, where 6 is the angle between wave vector and magnetic field, while the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…which have solitary or solitonic solutions. Using the reductive perturbation technique, ion-acoustic solitons have been studied by the numbers of authors (Bharuthram and Shukla 1986;Yadav and Sharma 1991). In contrast to the usual plasmas that consisting of electrons and positive ions, it has been observed that the nonlinear waves in plasmas which containing additional components such as positrons behave differently (Rizzato 1988).…”
mentioning
confidence: 99%
“…which have solitary or solitonic solutions. Using the reductive perturbation technique, ion-acoustic solitons have been studied by the numbers of authors (Bharuthram and Shukla 1986;Yadav and Sharma 1991). In contrast to the usual plasmas that consisting of electrons and positive ions, it has been observed that the nonlinear waves in plasmas which containing additional components such as positrons behave differently (Rizzato 1988).…”
mentioning
confidence: 99%
“…Ion acoustic solitary waves (IASWs), as one of the most important nonlinear excitations in plasma physics, have been studied by a number of authors in various models of plasma physics in the last few decades [2,3,8,23,30,40,78,82,86]. They arise due to a delicate balance between the dispersive and nonlinear properties of the medium.…”
Section: Introductionmentioning
confidence: 99%
“…The IA solitons have been observed experimentally by Ikezi et al [23] (also see Refs. [3,8,86]). The IA waves are highly Landau damped unless one considers the case T i ( T e [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of authors have been studied ion-acoustic solitary waves using the reductive perturbation technique in different plasmas (Bharuthram and Shukla 1986;Yadav and Sharma 1991). In contrast to the usual plasmas that consisting of electrons and positive ions, it has been observed that the nonlinear waves in plasmas which containing additional components such as positrons have different characters (Rizzato 1988).…”
Section: Introductionmentioning
confidence: 99%